IDENTIFIKASI FAKTOR PEMBATAS LINGKUNGAN PADA PERTUMBUHAN BAYAM MERAH - Candraningtyas, Callista; Indrawan, Muhammad (RISALAH KEBIJAKAN PERTANIAN DAN LINGKUNGAN Rumusan Kajian Strategis Bidang Pertanian dan Lingkungan, 2024)
Limiting factors are very important for plant growth. The aim of environmental limiting factor research is to examine several limiting factors and identify how significant the role of limiting factors is in plant growth. The way the work is done is to observe 4 variations which will be given different treatment. The method used is an experimental study with quantitative analysis, that is, each existing data is processed in tables and explained. The results of this research show significant differences, namely variation A1 has a height of 6.9 cm and a number of leaves of 7 pieces, variation A2 has a height of 19.8 cm with a number of leaves of 72 pieces, variation A3 has a height of 5.3 cm and a number of leaves of 7 pieces. , and the A4 variation has a height of 9.3 cm and a total of 24 leaves. Of all the variations carried out, it is proven that water, soil, air, temperature, and sunlight play an important role in plant growth. A policy recommendation that can be implemented is the use of screen houses. A screen house is a building made of plastic which functions to protect against pest attacks and supports direct sunlight exposure to plants.